Research and application of the IBN for the next generation internet - Xin ZHANG (Dianxin kexue)
Faced with the new business needs and complex market environment,traditional manual methods can no longer meet the existing needs,and more intelligent solutions are urgently needed.With the development of artificial intelligence and big data technology,IBN has become a means to solve the current problem.The background and research progress of the IBN were introduced,and the application of the IBN in the next generation internet was analyzed.